Sleep Apnea in Idiopathic Pulmonary Fibrosis: A Molecular Investigation in an Experimental Model of Fibrosis and Intermittent Hypoxia - Liasmine Haine; Juliette Bravais; Céline-Hivda Yegen; Jean-Francois Bernaudin; Dominique Marchant; Carole Planès; Nicolas Voituron; Emilie Boncoeur (Life, 2021)
Background: High prevalence of obstructive sleep apnea (OSA) is reported in incident and prevalent forms of idiopathic pulmonary fibrosis (IPF). We previously reported that Intermittent Hypoxia (IH), the major pathogenic element of OSA, worsens experimental lung fibrosis. Our objective was to investigate the molecular mechanisms involved. Methods: Impact of IH was evaluated on C57BL/6J mice developing lung fibrosis after intratracheal instillation of Bleomycin (BLM). Mice were Pre-exposed 14 days to IH before induction of lung fibrosis or Co-challenged with IH and BLM for 14 days. Weight loss and survival were daily monitored. After experimentations, lungs were sampled for histology, and protein and RNA were extracted. Results: Co-challenge or Pre-exposure of IH and BLM induced weight loss, increased tissue injury and collagen deposition, and pro-fibrotic markers. Major worsening effects of IH exposure on lung fibrosis were observed when mice were Pre-exposed to IH before developing lung fibrosis with a strong increase in sXBP1 and ATF6N ER stress markers. Conclusion: Our results showed that IH exacerbates BLM-induced lung fibrosis more markedly when IH precedes lung fibrosis induction, and that this is associated with an enhancement of ER stress markers.